Morphology and pitcher's color Nepenthes in Batu Lubang Sibolga Area, North Sumatra Province, Indonesia - MHD. RAFI’I MA’ARIF TARIGAN; SUHARTINI AZIS; INDAYANA FEBRIANI TANJUNG; CORNELI PARY; MIZA NINA ADLINI; UMMI NUR AFINNI DWI JAYANTI; ARDIANTO ARDIANTO; ANDI YURNI ULFA (Society for Indonesian Biodiversity, 2023)
Abstract. Tarigan MRM, Aziz S, Tanjung IF, Pary C, Adlini MN, Jayanti UNAD, Ardianto, Ulfa AY. 2023. Morphology and pitcher's color Nepenthes in Batu Lubang Sibolga Area, North Sumatra Province, Indonesia. Biodiversitas 24: 1953-1962. The study's objective was to identify the size, color, and shape of a pitcher of Nepenthes found in the Batu Lubang Sibolga region. Purposive sampling is used as part of an exploratory approach in this study. Plot-based Nepenthes observation was conducted in the Sitahuis District, Central Tapanuli Regency, North Sumatra Province, Indonesia, to examine pitcher morphology and color. The results showed two species of Nepenthes, namely N. gracilis Korth and N. eustachya Miq, with two types of pitchers each, namely the lower and upper pitcher. The morphology of the Nepenthes pitchers has an almost similar shape but differs in the size of the pitcher circumference, where the lower pitcher is smaller than the upper pitcher. The bottom pitcher of N. gracilis has redwood (45%), and the upper pitcher is light green (55%), according to the proportion of observations of the color of the lower and upper pitchers of these two species. While the upper pitcher of N. eustachya is green with red dots (70%), the lower pitcher is light reddish green (30%). According to the study's findings, Nepenthes in the Batu Lubang Sibolga area required conservation intervention to preserve this species.